2015
DOI: 10.3381/14-041r.1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Application Rate Influence on Yield, Quality, and Chemical Constituents of Flue-Cured Tobacco, Part I: Application Timing

Abstract: Research was conducted at 5 locations between 2012 and 2013 to determine the effect of nitrogen application rate and timing on yield, quality, and leaf chemistry of flue-cured tobacco. Urea-ammonium-nitrate was applied at 75, 100, and 125% of the recommended nitrogen rate for each specific field condition. All treatments were applied at differing intervals beginning at transplanting and concluding prior to or at topping. Yield data were collected postharvest, and leaf quality was determined according to U.S. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…The main effect of organic N source was not significant. Results are similar to Drake et al (2015a) which reported an increase in N concentration in leaf tissue sampled at layby in treatments receiving higher application rates of N prior to sampling.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The main effect of organic N source was not significant. Results are similar to Drake et al (2015a) which reported an increase in N concentration in leaf tissue sampled at layby in treatments receiving higher application rates of N prior to sampling.…”
Section: Resultssupporting
confidence: 79%
“…Base and B-treatments were not different from each other in this analysis. Nitrogen application rate and SPAD are sometimes correlated in tobacco production (Drake et al, 2015a(Drake et al, , 2015b. Organic N source did not affect SPAD measurements.…”
Section: Resultsmentioning
confidence: 96%
“…Side‐dress applications of Cl − and N were accomplished by opening a furrow adjacent to tobacco plants with a 140 Farmall tractor outfitted with a single belly‐mounted coulter and then hand applying a pre‐measured or pre‐calibarated fertilizer quantity. Immediately following fertilizer application, furrows were closed with a Danish tine‐rolling cultivator in a manner similar to that outlined by Drake, Vann, and Fisher (2015)…”
Section: Methodsmentioning
confidence: 99%
“…Kaiser et al [3] found that nitrate both in soil solution from tobacco field or in well water below tobacco crop was greater than that in natural conditions. Considering the negative effect that an excess N usually determines on cured product quality [43][44][45], the evaluation of tobacco growing conditions that improve N-use efficiency becomes indispensable.…”
Section: Introductionmentioning
confidence: 99%